PERANCANGAN SISTEM INFORMASI PENGGAJIAN PADA PT WANGSA INDAH NUSANTARA - Dina Merlinda Izzah; Trisnawati, Meli (Jurnal Teknologi dan Bisnis, 2020)
The payroll information system in Aldomaru still uses Microsoft Excel, so there are often difficulties in finding payroll data if at any time the data is needed and it takes a long time to make data reports. This causes inefficient processing of payroll data. So we need a computerized system for processing payroll data in Aldomaru. So that it can be used as a fast, precise and accurate information in the form of an application. The research methods used are analytical methods and fact-finding methods: interviews, observations, and literature studies. Design method through database design and database application. The result achieved is the introduction of a payroll database system that facilitates the performance of the payroll department of PT Wangsa Indah Nusantara. The conclusion of this study is that the design of a new database can facilitate the payment of salaries. The objectives of this study include: finding the obstacles faced by the employee payroll department at PT Wangsa Indah Nusantara, designing an employee payroll information system. In this design, the author uses Visual Basic.NET programming language with database format using Microsoft Access 2010. The result to be achieved is the design of a payroll information system for management to make it more efficient and effective in making decisions on matters relating to payroll. The conclusion of this paper is that with the Payroll Application, the payroll administration section can easily make reports.